Mental Health in Zimbabwe: Are there Lessons for South Africa? - Freeman, Melvyn (PINS-Psychology in Society, 2025)
The notions of an appropriate or relevant psychology and mental health service for South Africa has recently become a major issue of concern and debate (e.g. OASSSA conference on Apartheid and Mental Health 1986; Dawes 1986; Foster 1986). A potentially informative contribution to the debate is to look at and analyse Mental Health in other African Countries. This is not to say that any other country is exactly the same as South Africa and would therefore have answers directly applicable, but nor is South Africa so unique that it cannot learn from the experience of others. Zimbabwe could be regarded as a good starting point as it is a country which suffered many years of apartheid rule, where care was given inequitably and where, at least theoretically, this should have changed. Secondly, again at least in theory, consideration would be given to issues of individual and group democracy. And importantly, Zimbabwe is on South Africa’s borders and accessible to South African passport holders.